An Ultrasensitive Contact Lens Sensor Based On Self‐Assembly Graphene For Continuous Intraocular Pressure Monitoring. (12th May 2021) - Liu, Zhiduo; Wang, Gang; Ye, Chen; Sun, Hongyan; Pei, Weihua; Wei, Chunrong; Dai, Wen; Dou, Zhiqiang; Sun, Qingyu; Lin, Cheng‐Te; Wang, Yijun; Chen, Hongda; et al.
Abstract: Elevated intraocular pressure (IOP) is the leading cause of glaucoma. As glaucoma is an irreversible neurological eye disease, it is urgent to realize timely and accurate IOP detection for diagnostic and therapeutic purposes. Here, a contact lens sensor for continuous IOP monitoring using self‐assembly graphene (SAG), is developed. The combination of face‐to‐face water transfer printing and micro‐electromechanical systems technology can realize the batch preparation of such a sensor. The sensor has good light transmittance and temperature stability. It exhibits an ultra‐high IOP sensitivity of 1.0164 mV mm Hg −1 on a silicone eye, and 3.166 mV mm Hg −1 in vitro on the porcine eye with remarkable linearity. The sensitivity of the proposed sensor is high enough to be read by a commercial radio frequency identification read–write system for continuous wireless monitoring of IOP. Furthermore, the as‐prepared sensor can work as normal for 24 h in phosphate buffer saline. Abstract : The non‐invasive intraocular pressure (IOP) sensor, which combines a "fish scale"‐like graphene structure and an optimized Wheatstone bridge circuit, exhibits an unprecedented IOP sensitivity of 1.0164–3.166 mV mmHg –1 in vitro. The voltage response is high enough to be detected over a commercial wireless system. A face‐to‐face water transferring method is developed to realize batch production of the sensor.